Memaknai Kembali Misi Kristen terhadap Parmalim - Purba, Fredi Ardo (JURNAL LUXNOS, 2024)
This paper discusses the role of mission in the identity of the Christian church as well as the concept of mission that should go beyond the mere proclamation of the gospel to include an attitude of life, concrete help, struggle for human rights, and social involvement. Christian mission is often misinterpreted as an attempt to Christianise others. This research uses a qualitative research method with a literature study approach by analysing sources related to Christian mission towards Parmalim. The results show that Christian mission should emphasise love, peace, and justice, rather than simply Christianising others. In particular, in the context of ministry to the Parmalim, it is important to understand and respect their beliefs and establish a respectful dialogue. A re-understanding of Matthew 28:19-20 emphasises the importance of understanding the context, the overall message of the gospel, and the role of the church as an instrument of Christ's love and teaching. True Christian mission is to strive for peace, justice and love in the world, and to respect other religious beliefs as part of the call to realise the Kingdom of God on earth.